The Influence of Product Quality and Price on Purchasing Decisions through Purchase Intention as a Mediating Variable - Nurkhotimah, Siti; Puspitasari , Intan; Ishak, I. (Golden Ratio of Marketing and Applied Psychology of Business, 2026)
This study examines the effect of product quality and price on purchasing decisions, with purchase intention mediating variable among La Tulipe cosmetic consumers in Purworejo, Indonesia. The research addresses the growing competitiveness in the cosmetics industry, where consumers prioritize value and quality. A quantitative method was used with 100 respondents selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed through multiple linear regression, t-test, F-test, and Sobel test using SPSS. The results show that price significantly influences both purchase intention and purchase decision, while product quality affects purchase decision but not purchase intention. Purchase intention mediates the effect of price on purchase decision, but not the effect of product quality. These findings suggest that pricing plays a key role in shaping both interest and actual buying behavior, while product quality influences consumers more directly during the decision stage. This study offers practical insights for local cosmetic brands in developing effective marketing strategies that align with consumer expectations.